Design of patterned sapphire substrates for GaN-based light-emitting diodes - 王海燕 林志霆 韩晶磊 钟立义 李国强 (Chinese physics B, 2015)
A new method for patterned sapphire substrate （PSS） design is developed and proven to be reliable and cost-effective. As progress is made with LEDs＇ luminous efficiency, the pattern units of PSS become more complicated, and the effect of complicated geometrical features is almost impossible to study systematically by experiments only. By employing our new method, the influence of pattern parameters can be systematically studied, and various novel patterns are designed and optimized within a reasonable time span, with great improvement in LEDs＇ light extraction efficiency （LEE）. Clearly, PSS pattern design with such a method deserves particular attention. We foresee that GaN-based LEDs on these newly designed PSSs will achieve more progress in the coming years.